2019
DOI: 10.1002/etc.4609
|View full text |Cite
|
Sign up to set email alerts
|

Effect‐Directed Analysis of Progestogens and Glucocorticoids at Trace Concentrations in River Water

Abstract: Effect-based monitoring is increasingly applied to detect and-in conjunction with chemical analysis-to identify endocrine-disrupting compounds (EDCs) in the environment. Although this approach of effect-directed analysis has been successfully demonstrated for estrogenicity and androgenicity, data on progestogens and glucocorticoids driving endocrine disruption are quite limited. We investigated progestogenic and glucocorticoid activities in Danube River water receiving untreated wastewater from Novi Sad, Serbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 60 publications
1
39
0
1
Order By: Relevance
“…Levels of significance were *p < 0.05, **p < 0.01, and ***p < 0.001. Median values, interquartile ranges, minimum and maximum are given in Additional file 1: Table S5 pharmaceuticals, industrial chemicals, pesticides, and personal care products in the Danube River in this area, to activate toxicity pathways and disturb biochemical and physiological homeostasis in various cell lines, zebrafish embryos and fish [22,[42][43][44][45]. Still, the questions whether the biological effects observed in vitro can be regarded as an indication of probable ecological impact and weather the impact could be confirmed by adverse effects in resident biota, on individual and population/community level remain open.…”
Section: Confirmation Of Exposure Of a Brama Population From Urban Amentioning
confidence: 99%
“…Levels of significance were *p < 0.05, **p < 0.01, and ***p < 0.001. Median values, interquartile ranges, minimum and maximum are given in Additional file 1: Table S5 pharmaceuticals, industrial chemicals, pesticides, and personal care products in the Danube River in this area, to activate toxicity pathways and disturb biochemical and physiological homeostasis in various cell lines, zebrafish embryos and fish [22,[42][43][44][45]. Still, the questions whether the biological effects observed in vitro can be regarded as an indication of probable ecological impact and weather the impact could be confirmed by adverse effects in resident biota, on individual and population/community level remain open.…”
Section: Confirmation Of Exposure Of a Brama Population From Urban Amentioning
confidence: 99%
“…Therefore, we felt it was important to assess these 2 types of bioassays in the EDA framework ( Figure 1). The 3 remaining studies employed fluorescence resonance energy transfer in cell-based Gene-BLAzer assays or vitellogenin messenger (m)RNA expression in primary rainbow trout hepatocytes (listed as "Other" bioassay in Table 1; Lavado et al 2009;Hashmi et al 2018Hashmi et al , 2020. Although the tg(CYP19a1b)-GFP zebrafish bioassay has been utilized in an EDA of EACs from sediment samples (Fetter et al 2014), we could not find any studies incorporating transgenic zebrafish in an EDA of EACs from water; nevertheless, we chose to include this bioassay in our EDA framework for comparative purposes against the other 2 selected bioassay types (yeast and LucTA).…”
Section: Literature Review Resultsmentioning
confidence: 99%
“…Lastly, although the GeneBLAzer cell assays were not assessed in our framework, the 2 EDA studies that utilized these assays (listed as "Other" in Table 1) also identified several of the EACs listed in Table 3 as active components in fractionated and whole sample. For example, P4 was identified as one of the 2 primary progestogens responsible for activity in fractionated river water (Hashmi et al 2020). Similarly, E2 was identified as the main estrogen responsible for much of the activity in different fractions of the same river water, and testosterone partly explained androgenic activity in fractions in that same study (Hashmi et al 2018).…”
Section: Detection Approaches For Edamentioning
confidence: 99%
See 2 more Smart Citations